Investment policies of life insurance companies - Jones, Lawrence D.; Capital Markets Project (Boston: Division of Research, Graduate School of Business Administration, Harvard University, 1968)
This project attempts to explain the way in which the whole set of interactions among households, nonfinancial businesses, governments and their agencies, and financial intermediaries produces a balance between the supplies and demands for securities of various types. The objective is to bridge the gap between the formal theoretical literature and the statistical and descriptive literature of capital markets with an analysis of the process by which investment flows are actually brought into balance in the capital markets.
Prepared under the auspices of the Capital Markets Project.
Includes bibliographical references: p. [545]-555.
ne 04/05/2018
Loans
Keywords: Insurance Companies---Investments.; Life Insurance--Finance.